History as critique: Collective representation in constructing the pasts of adult education - Arthur L. Wilson; Kenneth E. Melichar (Adult Education Research Conference, 1994)
If we are to understand who we are as educators in the present as well as who we hope to become, then we must examine and critique how we have collectively represented who we have been.